Palaeogenetic study of human migrations around the Caspian Sea during protohistory - Perle Guarino-Vignon (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The influence of human migrations on the genetic diversity of human populations around the Caspian Sea has been widely proven and studied. However, the history of the populations of Central Asia, and more specifically the Indo-Iranian-speaking populations, is still largely unknown. Our analyses based on modern and ancient DNA genomic data show that the present-day Indo-Iranian-speaking populations, the Tajiks and the Yaghnobis, display a strong genetic continuity with the Iron Age populations of southern Central Asia. These analyses show a recent and restricted gene flow from the Lake Baikal region for the Yaghnobis and Tajiks, and other minor gene flows for the Tajiks. Our study of the Turkmen also reveals an interesting case of change in language and cultural practices with no significant gene flow. Finally, this study presents new results allowing a better characterisation of the admixture that occurred in southern Central Asia during the transition between the Bronze Age and the Iron Age, a pivotal period for the history of the present-day populations of this region.